Modern state for stocks of Sakhalin-Hokkaido herring Clupea pallasii at the coast of Sakhalin Island and southern Kuril Islands - E. R. Ivshina (Известия ТИНРО, 2022)
Data of bottom trawl surveys at southwestern Sakhalin and surveys of the herring spawning grounds at southern Sakhalin and Kuril Islands are summarized, with assessment of the spawning grounds size and the eggs density in clutches. Fishery statistics and media reports are overviewed, as well. The stock of the Sakhalin-Hokkaido population increases since 2015, both off southwestern and southeastern coasts of Sakhalin, in the Aniva Bay, and at southern Kuril Islands. Number of the spawning herring increases everywhere within the Russian waters, as well as the size of spawning grounds and the density of eggs laying. In particular, the biomass of spawning herring was estimated in 2020 as 35.5 . 103 t at southwestern Sakhalin and 62.5 . 103 t at southeastern Sakhalin; it was 21.6 . 103 t in the Aniva Bay in 2021; the total catch of herring in the waters at Sakhalin Island and southern Kuril Islands reached 8.3 . 103 t in 2021. The stock of Sakhalin-Hokkaido herring is restoring after long depression, so this species is capable to return to the list of the major objects for fishery in the Sakhalin- Kuril region of Russia.